2014
DOI: 10.1007/s13744-014-0222-0
|View full text |Cite
|
Sign up to set email alerts
|

Insect Pests Occurring on Dacryodes edulis (Burseraceae) in Rural Areas in Gabon

Abstract: The inventory of pests occurring on Dacryodes edulis (Burseraceae) was carried out in rural areas in Gabon during 2009 and 2010. Yellow traps and visual observations were used to record weekly pests during the tree flowering stage, in five villages. Catches from yellow traps rose to 7,296 and 1,722 insect pests in 2009 and 2010, respectively, whereas records from visual observations corresponded to 1,812 and 171 insect pests in 2009 and 2010, respectively. During both years, abundance from traps and visual mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
4
0
1
Order By: Relevance
“…CFARQ primers with C. rosa, C. anonae or C. quilicii samples resulted in Tp values between 29 and 38 minutes with a Ta of 80.7°C (SD, 0.2) and LAMP amplification with CFARQ primers did not occur with other tephritid samples tested ( Figure 2 , Table S1). LAMP amplification was also not observed with Zaprionus ornatus , an unrelated fruitfly that feeds on plant hosts on which Ceratitis capitata also occurs ( Poligui et al., 2014 ) (Johan Witters, pers. communicaton) (Figure S4).…”
Section: Resultsmentioning
confidence: 99%
“…CFARQ primers with C. rosa, C. anonae or C. quilicii samples resulted in Tp values between 29 and 38 minutes with a Ta of 80.7°C (SD, 0.2) and LAMP amplification with CFARQ primers did not occur with other tephritid samples tested ( Figure 2 , Table S1). LAMP amplification was also not observed with Zaprionus ornatus , an unrelated fruitfly that feeds on plant hosts on which Ceratitis capitata also occurs ( Poligui et al., 2014 ) (Johan Witters, pers. communicaton) (Figure S4).…”
Section: Resultsmentioning
confidence: 99%
“…Arg. (Euphorbiaceae) and Dacryodes edulis (G.Don) H. J. Lam (Burseraceae), from Congo to Franceville [17,18] . In this context, infested leaves of avocado could have been transported from a nearest neigboring country to Gabon.…”
Section: Symptoms and Pest Injury Levelmentioning
confidence: 99%
“…It presence is a new event for avocado orchards, and a serious threat for fruit trees culture. This insect is newly observed in Franceville and Gabon, because former studies did not allow to observe it [17,18] . There is also no literature awarning about it occurrence in Africa.…”
Section: Diagnosismentioning
confidence: 99%
“…The scientific research on D. edulis focused on the characterization of the nutritive value of its pulp and its oil 6 , the oil extraction processes 7 and D. edulis tree of propagation techniques 8 . These revealed excellent nutritional qualities of the fruit pulp and interesting food processing properties of the oils extracted from the pulp and kernel safou 9 . The pulp, the only edible part of the fruit is particularly rich in lipids, indicated that safou could be an important source of oil 10 .…”
Section: Introductionmentioning
confidence: 95%